Improving Teacher Competence Using Independent Teaching Application Completing Learning Content Based ICT in Ceria Pantai Labu Kindergarten - Togi Van Jaya S; Saut Purba; Sukarman Purba (Journal of Education and Teaching Learning, 2023)
The Merdeka Mengajar Platform is a technology platform that is provided to become a driving partner for teachers and principals in teaching, learning and work. The use of technology platforms in the world of education is very necessary both in the learning process and in the management process at school. Teachers are expected to be able to improve competence, one of which is in mastering Information and Communication Technology (ICT). An activity or training needs to be held to increase teacher knowledge/insight and skills about ICT. The training is expected to be applied by teachers in using independent teaching applications and the use of information technology media in teaching and learning activities. The purpose of this study is to improve teacher pedagodic competence and the ability of teachers to use independent teaching platforms and fill in ICT-based learning content. The methods used in this training are lectures, demonstrations and practice. The data collection technique uses a questionnaire regarding the participants' perceptions of the training implementation. Indicators of the success of this training include the level of learning, level of behavior, level of reaction and level of results. The results obtained from data processing of all indicators are that participants agree that the implementation of the training has gone well, where most of the participants are of the view that the implementation of the training has provided profound benefits and is very helpful in improving the quality of the participants themselves.